Milton on film - Brown, Eric C., 1971- (Medieval and Renaissance literary studies., 2015)
"The history of Milton on film, and Paradise Lost in particular, has been full of ambitious visions and dazzling failures, and this book explores all, from the earliest proto-cinematic inventions to the contemporary age of sprawling digital cinematography and Hollywood blockbusters"--